MANAGING STRESS AND EMOTION IN PENCAK SILAT ATHLETES - dandy, Dandy; Jalil, Rasyidah; Kahar, Irsan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
The research is based on the importance of mental toughness in the achievement of martial arts athletes. The function of mental toughness and emotional control is to maintain performance in the face of adversity. This study aims to find (1) a description of the emotional and stress training model for pencak silat martial arts athletes (2) a description of emotional processing and its impact on the success of pencak silat martial arts athletes, and (3) a description of the operational model of emotional and stress control in pencak silat martial arts athletes. . The sample in this study were the pencak silat athletes from the city of Palopo. The method used in data collection is qualitative. The research subjects were 7 informants consisting of 2 coaches and 5 athletes. The sample criteria that must be met are as follows: (1) parents living in the same house as athletes (2) male and female (3) athletes aged 18 – 22 years. Results of this study Based on the description of the results of the study, overall the martial arts athletes in this study showed quite good attitudes and behavior, seen from their self-confidence, stress management and good emotions. The description states that the emotional aspect as central to one's life needs important attention by coaches and parents, so that a comprehensive understanding of the development of children's emotional stimulation is needed.